Analysis Of Accounting Information Systems In Managing Education Unit Operational Assistance Funds (Bosp) Using E-Rkas At Smp Negeri 12 Buru - Trisna Prasetyaningrum; Christina Sososutiksno; Dwi Haryanti (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the implementation of the Accounting Information System (AIS) in the Education Unit Operational Assistance (BOSP) fund management cycle at SMP Negeri 12 Buru, which includes the planning, implementation, and evaluation stages using the e-RKAS application. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, participatory observation, and documentation studies. The results show that the planning stage is carried out through the preparation of e-RKAS based on the results of the School Self-Evaluation (EDS) and the educational profile. In the implementation stage, fund management has integrated manual and digital bookkeeping systems through the ARKAS application in accordance with the regulations of the Minister of Education, Culture, Research, and Technology No. 63 of 2022. Evaluations are conducted periodically to ensure transparency and accountability to stakeholders. Although this digital system improves administrative efficiency, the main obstacles identified are limited human resource technological competency and the stability of internet infrastructure at the research location. This study recommends the need for ongoing training for the BOSP management team to optimize the system..